On pornography and its impact on sexual violence - Bilokapić, Šimun (Array, 2021)
Having offered a short presentation of the phenomenon of pornography, in particular its common, yet ominous presence in the means of social communication, the paper focuses on the analysis of the relationship between pornography and sexual violence. By employing theories of family violence and especially, theories of sexual violence, the paper examines connection between pornography and sexual violence, analyses offsetting "pro et contra" views concerning this interrelation, and possible interests lying behind contrary arguments. The paper proceeds with a detailed analysis of the document issued by the Pontifical Council for Social Communications "Pornography and Violence in the Communications Media", followed by an anthropological and ethical analysis of the relationship between pornography and sexual violence. The deceit and deception of the dilemma lies in the fact, the paper concludes, that pornography and sexual violence are not only in a causal relationship, but these are two very similar phenomena, almost the same by (their) nature and content, the result of the same mentality and culture with the same devastating effects on a person and person"s sexuality.